Risk Factors, Prognostic Factors, and Nomogram for Distant Metastasis in Breast Cancer Patients Without Lymph Node Metastasis - Min, Yu; Liu, Xiaoman; Hu, Daixing; Chen, Hang; Chen, Jialin; Xiang, Ke; Yin, Guobing; Han, Yuling; Feng, Yang; Luo, Haojun (Frontiers in Endocrinology, 2021)
Background: Lymph node negative (N0) breast cancer can be found coexisting with distant metastasis (DM), which might consequently make clinicians underestimate the risk of relapse and insufficient treatment for this subpopulation. Methods: The clinicopathological characteristics of N0 breast cancer patients from the Surveillance, Epidemiology, and End Results (SEER) database between Jan 2010 and Dec 2015 were retrospectively reviewed. Multivariate logistic and Cox analyses were used to identify independent risk factors in promoting DM and the 1-, 3-, and 5- year cancer-specific survival (CSS) in this subpopulation. Result: Seven factors including age (<40 years), tumor size (>10mm), race (Black), location (central), grade (poor differentiation), histology (invasive lobular carcinoma), and subtype (luminal B and Her-2 enriched) were associated with the DM and the area under curve (AUC) were 0.776 (95%CI:0.763-0.790). Moreover, T1-3N0M1 patients with age (>60 years) at diagnosis, race (Black), subtype (triple-negative breast cancer), no surgery performed, and multiple DMs presented a worse 1-, 3-, and 5- year CSS. The areas under the ROC for 1-, 3-, and 5- year CSS in the training cohort were 0.772, 0.741, and 0.762, respectively, and 0.725, 0.695, and 0.699 in the validation cohort. Conclusion: The clinicopathological characteristics associated with the risk of DM and the prognosis of female breast cancer patients without lymph node metastasis but DM are determined. A novel nomogram for predicting 1-, 3-, 5- year CSS in T1-3N0M1 patients is also well established and validated, which could help clinicians better stratify patients who are at a high-risk level for receiving relatively aggressive management.